RELEVANSI KONSEP AKAL DALAM AL-QUR'AN BAGI NEUROSAINS PENDIDIKAN ISLAM - Laskita Dewi, Maya; Katni Katni; Riyanto; Ayu Wulandari (LPPM STAI Muhammadiyah Probolinggo, 2024)
This paper supports the exposing of the concept of reason in the Koran as the basis for the development of Neuroscience. This research is a library research using descriptive analysis by collecting data, compiling, clarifying, compiling and interpreting. The technical analysis used is analytical descriptive. The findings of this study are that the Koran uses the term ‘aql which has various powers possessed by humans. Intellect is an organ that has active and conscious power, binds and holds the object of science with symbolic words or forms, words or actions. Neuroscience is a neuroscience that discusses the nervous system, most neurons or nerve cells with multidisciplinary. Neuroscience is one of the special sciences that studies the knowledge of the nervous system. Neuroscience has a basis in Islam, the Koran. Islamic education can be developed from neuroscience studies and the Koran. Therefore, Islamic education can be integrated-interconnected in the development of research with the analysis of the terms in the Koran and neuroscience.